A Ring-D-Seco-Tetranortriterpenoid from Seeds of Carapa procera Active against Breast Cancer Cell Lines - Dioum, Mbaye Diaw; Seck, Matar; Silvestre, Virginie; Planchat, Aurélien; Loquet, Denis; Lohard, Steven; Barille-Nion, Sophie; Remaud, Gerald S; Robins, Richard J; Tea, Illa (Planta Medica, 2016)
The seeds of Carapa procera are exploited extensively in West African ethnopharmacy for the treatment of several pathologies, including inflammation. They also are effective as insect antifeedants and as a mosquito repellent. With the aim of identifying bioactive principles, an ethyl acetate extract of the defatted seeds was made and fractionated. Two principle compounds were isolated. One of these, 5,6-dehydro-7-deacetoxy-7-oxogedunin (1), while known from another genus of the Meliaceae, is newly identified from the genus Carapa and its X-ray structure is described for the first time. In addition, 1 displayed strong anti-clonogenic activity at 10 µM. The other compound, mexicanolide (2), is known from this species and showed neither cytotoxicity nor anti-clonogenicity. These differences in efficacy are discussed in relation to known structure-activity relationships of limonoids.
Keywords: Carapa procera; Meliaceae; phytochemistry; tetranortriterpenoid; limonoid; breast cancer; cell death; clonogenicity